2013
DOI: 10.1007/978-1-4614-8483-7_14
|View full text |Cite
|
Sign up to set email alerts
|

Crowd Counting and Profiling: Methodology and Evaluation

Abstract: Video imagery based crowd analysis for population profiling and density estimation in public spaces can be a highly effective tool for establishing global situational awareness. Different strategies such as counting by detection and counting by clustering have been proposed, and more recently counting by regression has also gained considerable interest due to its feasibility in handling relatively more crowded environments. However, the scenarios studied by existing regression-based techniques are rather diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(92 citation statements)
references
References 82 publications
(129 reference statements)
0
92
0
Order By: Relevance
“…Loy et al [80] studied as well as compared the state-of-theart regression methods dealing with many co-linearity among features. They found that feature selections are important and depend on crowd scene.…”
Section: E Video Datamentioning
confidence: 99%
“…Loy et al [80] studied as well as compared the state-of-theart regression methods dealing with many co-linearity among features. They found that feature selections are important and depend on crowd scene.…”
Section: E Video Datamentioning
confidence: 99%
“…an indicator of fighting, rioting, violent protest, mass panic and excitement [4], [5];  business intelligence and behavioural economics applications; e.g. the distribution of costumers may be used for product placement, floor planning and staff management [6]. In addition, the overall crowd in a retail store may be monitored to assess store performance over time [7];  Transport applications; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The low-level features are used with the proposed system to describe the visual properties in the frames as texture, edge, shape, size and colour [5], [53]. Blob size histogram and edge orientation histogram are also used with the proposed system as intermediate features between low and high-level features.…”
Section: B Feature Representation and Selectionmentioning
confidence: 99%
“…They are the general description of a frame and have a strong relationship with the crowd size [5]. local binary pattern (LBP) and Gray-level co-occurrence matrix (GLCM) are usually used to find texture features [5], [54], [55].…”
Section: ) Texture Featuresmentioning
confidence: 99%
See 1 more Smart Citation